Numerical Taxonomy of Two New Mite Species of the Genus Caloglyphus Berlese (Acaridae) from Pakistan (Biological Sciences - PJSIR, 2005)
During the mite sampling of the genus Caloglyphus, the taxonomical analysis of diagnostic features of the hypopial stage confirmed two new taxa named as C. agrios and C. hadros. When compared with the already known worldwide species within this genus, these species showed sufficient dissimilarity to be classified as separate taxa. The characteristic features differentiating these new species from the other Caloglyphus species are the shapes of gnathosoma, propodosoma, hysterosoma, apodemes, coxal fields, suctorial shield, and chaetotaxy and solenidiotaxy of legs. The present study reports the historical review of the genus, completed with the information on already known species, their descrip- tion, illustration of main characters, geographical distribution, host range, remarks on the new species, matrixes showing comparisons, and the percentage of similarity along with a key for their identification based on hypopial characters for the species known from Pakistan.